Ruptured Baker's cyst with compartment syndrome: an extremely unusual complication. (20th December 2012) - Hamlet, Mark; Galanopoulos, Ilias; Mahale, Avinash; Ashwood, Neil
Abstract : A 69-year-old man presented with sudden onset of pain with acute tense swelling of his left leg. Initially he was treated empirically with antibiotics for cellulitis while the possibility of deep vein thrombosis was ruled out. His symptoms gradually worsened with progressive distal neurological deficit and increasing pain. Further investigations suggested that he had a ruptured Baker's cyst in the calf with development of compartment syndrome.